EFEKTIVITAS MEDIA LOOSE PARTS TERHADAP KEMAMPUAN KOLABORASI ANAK USIA DINI - Anindya Wanda Prameswari; Naili Rohmah (Bunayya, 2026)
The issues identified in this study are that children tend to complete tasks individually without involving their peers, communication in completing joint tasks is still lacking, and children do not consistently participate in group activities. Additionally, children are not yet able to share materials. The study aims to examine the effect of using loose parts on improving collaboration skills in early childhood; this study employs a quantitative approach. The research design used is a pre-experimental one-group pretest-posttest design. This study involved all children in Group B, consisting of 26 children aged 5 to 6 years. Data analysis utilized several statistical tests, including the Shapiro-Wilk normality test and the paired-sample t-test. Data processing revealed an increase in the mean pretest score, which rose from 25.1 to 42.9 on the posttest. The Sig. (2-tailed) value obtained from the paired-sample t-test was 0.000 < 0.05, indicating a significant increase. The results of the study show a significant improvement in collaboration skills following the use of loose parts. Loose parts can be utilized as an alternative learning medium that supports children’s collaboration skills and social interaction.